Awards and hopes - Mohd Azmyl, Md Yusof * (The Malaysian Insight, 2023)
FEEL-GOOD news of the week: Amanda Nell Eu’s feature film debut “Tiger Stripes” on Wednesday won the Grand Jury Prize at the Cannes International Critics’ Week.